A Critical Review of the Trading of Surplus Renewable Energy in the Context of a Proposal for a Universalization System - Abdon Campos dos Santos; Toni Alex Reis Borges; Filipe Cardoso Brito; Hugo Saba; Aloísio Santos Nascimento Filho (JOURNAL OF BIOENGINEERING, TECHNOLOGIES AND HEALTH, 2026)
The growing participation of prosumers in the energy matrix has challenged the traditional models of regulation of the Brazilian electricity sector. This article presents a critical review of the current legislation, especially Law 14,300/2022, which regulates distributed micro and minigeneration, allowing credit compensation for the surplus of energy generated, but without enabling its free commercialization in the market. The limitations of the current remuneration model and the legislative proposals under discussion in Brazil are explored, such as Bill 4530/2019 and the sectoral reform planned for 2025–2028. In this context, it is proposed the development of a System for the Universalization of the Commercialization of Renewable Energy Surpluses, which is intended to unify and streamline the management of distributed generation credits, with the possibility of fostering innovation and sustainability in the Brazilian electricity sector.